Transformational Leadership as a Strategy to Improve Working Relations in Schools through Islamic Values - Husnurijal; Indah Rahmawati; Nurul Putri; Efrita Norman (MES Bogor, 2024)
The research investigates the role of transformational leadership as an effective strategy for improving working relationships in schools by integrating Islamic values. The study explores how leadership that motivates, inspires, and empowers individuals within the educational environment can create a positive work atmosphere. Islamic values such as honesty, cooperation, mutual trust, and responsibility are central to building harmonious relationships among teachers, students, and the broader school community. The research employs a systematic literature review methodology, gathering data from academic journals, books, and relevant articles. The principal findings suggest that transformational leadership based on Islamic values not only enhances collaboration but also fosters a warm, empathetic, and supportive school environment, contributing to both character development and academic success. In conclusion, transformational leadership, underpinned by Islamic values, plays a critical role in fostering a cooperative and trust-based school culture. This leadership model positively impacts the broader educational system, making it a significant contribution to the field of educational leadership, especially within Islamic education contexts.